FAST-FISH with laser beam microdissected DOP-PCR probe distinguishes the sex chromosomes of Silene latifolia - Hobza, Roman; Lengerova, Martina; Cernohorska, Halina; Rubes, Jiri; Vyskot, Boris (Chromosome research, 2004)
We present an improved FISH strategy for differentiating the sex chromosomes of the dioecious model plant, Silene latifolia. Fixed mitotic protoplasts were dropped on a polyethylene naphthalate membrane, the X or Y chromosomes were isolated using nitrogen laser beam microdissection, catapulted by laser pressure, and amplified by DOP-PCR. A modified FAST-FISH protocol based on a short hybridization time combined with a low concentration of probe was used. The success of this approach is demonstrated by the differential labeling of the X and Y chromosomes and it could represent a quick method for comparing organization of plant genomes.
Keywords: lasery; Carbocyanines; DNA Probes; Sex Chromosomes; Fluorescent Dyes; polymerázová řetězová reakce; pohlavní chromozomy; in situ značení DNA s primerem; Silene; Lasers; hybridizace in situ fluorescenční; Metaphase; mikrodisekce; Protoplasts; chromozomy rostlin; Chromosomes, Plant; Primed In Situ Labeling; Microdissection; karbocyaniny; protoplasty; fluorescenční barviva; metafáze; DNA sondy; In Situ Hybridization, Fluorescence; Polymerase Chain Reaction